Para que servem as eleições municipais? Estratégias políticas na competição local - Martins, Thaís Cavalcante (2021)
The objective of this research is to investigate the strategies of political actors in local electoral competition, focusing on two dimensions. The first concerns legitimate and formal means, with an emphasis on the provisions established by the electoral system that increase one's chances of accessing power. It also explores the levels of competition as well as the conditions of competition. The second dimension delves into the instruments that enable candidates and parties to monitor elections and the occurrence of electoral irregularities. Such devices are assessed as a political strategy available to candidates and parties both before and after voting. The general hypothesis is that variation in strategy use is related to factors exogenous to elections, but it is also due to institutional factors, such as the level of competitiveness in municipal disputes. Based on an analysis of electoral, socioeconomic, and jurisprudence data, descriptive statistics and logistic regression techniques were used to investigate the variation and test the hypothesis. The study focuses on the dispute for the municipal executive position between 2000 and 2016, covering all Brazilian municipalities. The findings support the hypothesis and demonstrate that, even though elections have become more competitive and monitored, they continue to coexist with abusive practices, which are not necessarily limited to the country's less developed territories.